Tipping point dynamics in global land use. (14th December 2021) - Taylor, Charles A; Rising, James
Abstract: Agricultural land use has recently peaked, both globally and across country income groups, after centuries of expansion and intensification. Such shifts in the evolution of global land use have implications for food security, biodiversity loss, and carbon emissions. While economic growth and land use are closely linked, it is difficult to determine the extent to which the relationship is causal, deterministic, and unidirectional. Here we utilize gridded datasets to study long-term global land use change from 1780 to 2010. We find evidence for an economic tipping point, where land use intensifies with economic development at low income levels, then reverses after incomes reach a critical threshold. Cropland peaks around 5000 GDP per capita then declines. We utilize a Markov model to show that this reversal emerges from a variety of divergent land use pathways, in particular the expansion of protected areas and a reduction in land use lock-in. Our results suggest that economic development remains a powerful driver of land use change with implications for the future of natural ecosystems in the context of continued population and income growth.